Narasi Stratifikasi Sosial Novel Trilogi Sembilu dalam Taman Karya Ngurah Parsua - Dea Adelia Putri, Ni Kadek; Darma Putra, I Nyoman (Humanis; Vol 22 No 1 (2018)DO - 10.24843/JH.2018.v22.i01.p05, 2018)
The trilogy novel ‘ Sembilu d alam Taman ’ is analyzed using structural theory, and the sociology of literature theory. The using of sociology of literature theory in this study is because the trilogy novel ‘ Sembilu d alam Taman ’ has a strong social view on the characters. There are three formulations of the problems discussed, namely: the analysis of structure, The relationships between structure and aspects of sociology of literature, and social stratification. The purpose of this research is to know structure, the relationship between structure and sociology aspect, and social stratification of characters in the novel. There are three methods and techniques used in the study, namely: (1) methods of data collection, used qualitative methods and reading techniques, observation, and record; (2) Methods of data analysis using analytical descriptive method followed by observation  and record techniques; and (3) Method of the result of data analysis using description method and presentation technique result of data analysis presented in thesis preparation format. There are three results of the research, those are the analysis of structure, the relationships between structure and aspects of sociology, and social stratification of the characters. The primary character in this novel is Lodra. In addition, there are secondary characters and complementary characters. The plot in the novel is divided into five stages. Starting with the introduction of the character of Lodra, the conflict is experienced by the character, and ends with the stage of resolution of which Lodra lives happily with Sylvei. There are three settings in the story those are the dominant setting of place in Bali, the setting of time is morning, afternoon, evening, and the social setting is the people of Bali. The structure of the novel is related to the sociological aspects of literature. The aspect is divided into three namely, the behavior of rural and urban society, social status, and education. The caste system is a social stratification narrated in this novel. There are three castes found, namely, brahmins, ksatrya, and sudra. Some characters have different views about their social status. Figure Lodra who disagreed with the rules of caste, while his father was very obedient to the caste system. In the end, Lodra's father abandoned the caste rules. That was due to an increasingly advanced era and an already educated society.